STRATEGY FOR INCREASING THE CAPACITY OF VILLAGE APPARATUS HUMAN RESOURCES IN USING TECHNOLOGY BASED VILLAGE INFORMATION SYSTEMS (TANGEBAN VILLAGE, MASAMA DISTRICT, BANGGAI REGENCY) : Strategi Peningkatan Kapasitas SDM Aparatur Desa dalam Penggunaan Sistem Informasi Desa Berbasis Teknologi (Desa Tangeban Kecamatan Masama Kabupate Banggai) - Tasman Malusa; Muhlin Muhlin; Muhamad Irsan S. Nang; Noprianto Noprianto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to identify strategies for increasing the capacity of village apparatus human resources in the management of technology-based village information systems in Tangeban Village, Masama District, Banggai Regency. The problem faced by this village is the low mastery of information technology among village officials, which hinders data management, development planning, and budget transparency. Although technology has been applied to improve the quality of public services, limited skills, lack of continuous training, and lack of infrastructure are the main obstacles. This study uses a descriptive qualitative method, with data collection through direct observation, interviews, and document analysis. This method aims to analyze the challenges, experiences, and strategies for increasing the capacity of village officials in operating technology. The results of the study show that technology training, improvement of bureaucratic management, and the provision of adequate infrastructure are needed to improve the efficiency of village administration management. Improving the competence of village officials through relevant training can improve the performance of village government, accelerate services, and increase transparency and responsiveness to community needs. The findings also show that there is a variation in technology understanding among village officials, with most of them understanding technology well, while some groups still need to increase their knowledge to optimize the use of technology-based village information systems.